Effects of dynamic gradient compression from ski performance garments on perceptuel indicators in cross country skiing - McLaren, J.; Teng, P. S. P.; Heil, D. P. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
In recent years the prevalent use of gradient compression garments (CG) within the medical and sporting fields is apparent. However, data on compression values from wearing CGs statically and dynamically are often not indicated in studies and such effects are not well understood. Furthermore, there is limited research which has focused on analyzing the use of CGs for cross country (XC) skiing.